KEMATANGAN GONAD IKAN SEPAT MUTIARA (Trichogaster leeri Blkr) DENGAN PEMBERIAN PAKAN YANG BERBEDA - Habibi .; Sukendi .; Neti Aryani (Universitas Sriwijaya, 2013)
The research was conducted from March to May 2013 in Bredding and Hatchery Laboratory of Fishery and Marine Science Faculty of Riau University. The aim of this research was to investigate suitable feed for the maturation of the gonads of sepat mutiara (Trichogaster leeri Blkr) reared with different feeding treatment such as Gonad Maturity Level (TKG), gonad maturation index (IKG), fecundity, egg diameter and egg maturation. The research method used was Completely Randomized Design (CDR) with three treatments and three replications. The treatment in this study were P1 (Tubifex sp), P2 (Shrimp pellet), P3 (Shrimp pellet + Vitamin E). The result showed that good feed for the maturation of the gonads was shrimp pellets + Vitamin E, reared for 42 days and the total fish reached TKG IV 29 tails , index gonad somatic 9,32 %, fecundity of 2646 eggs, egg diameter 0.70 mm. The temperature range from 26 – 280 C, pH 5 – 6, DO 4.0 – 5,0 ppm. Keyword: different feed, Gonad maturation, Trichogaster leeri Blkr